ANALISIS HARGA SAHAM PERUSAHAAN OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA - Nurulhuda, Elly Soraya; Lutfiati, Anis; Setiawan, Topan (Kinerja, 2021)
The purpose of this study is to analyze the factors affecting stock prices, empirical study of manufacturing companies in the automotive and component sectors on the Indonesia Stock Exchange for the period 2011-2019. This research. using purposive sampling with a sample of 9 automotive and component companies. The data used in this study, in the form of secondary data. Using panel data regression with Eviews 9. The results of the research variable Earnings Per Share (EPS), Price Earning Ratio (PER), and Dividend Per Share (DPS) have a significant effect on stock prices. Earning Per Share (EPS) has no significant positive effect. Price Earning Ratio (PER) has a significant positive effect, and Dividend Per Share (DPS) has a positive and insignificant effect. The coefficient of determination (R Square) of EPS, PER, and DPS on the stock price is 84%. Proving that EPS, PER and DPS explain 84% of Beta Shares, while the remaining 16% is due to other factors outside the variables studied